Changes in muscle architecture and tendon compliance after a bout of eccentric contractions - Vieillevoye, S.; Boucher, C.; Duchateau, J.; Carpentier, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Unaccustomed eccentric exercise induces muscle soreness and alterations in muscle cellular structure (Ishikawa et al., 2006). The aim of the present study was to investigate the changes in muscle architecture and tendon compliance during muscle contraction and passive stretching after eccentric contractions. Methods: Ten male subjects performed a training session with the right calf muscles, consisting in 10 sets of 10 eccentric contractions at 120% of 1RM. Subjects were tested at baseline and immediately, 2 hours (H+2), 2 days (D+2), 4 days (D+4) and 7 days after the session. Muscle architecture and tendon compliance were investigated using ultrasonography (Abellaneda et al., 2009; Chen et al., 2006). Fascicle length (FL) and pennation angle (PA) of the Gastrocnemius Medialis muscle and Achilles tendon elongation (TE) were recorded, respectively, during passive stretching and muscle contraction at different torque levels. During passive stretching, the ankle joint was moved from -10° to +30° of dorsiflexion. Isometric contractions of the plantarflexor muscles were performed with the ankle joint in neutral position (90°). Results: Isometric torque during MVC was reduced (22±9%; P<0.001) immediately after the eccentric contractions. Maximal torque was still significantly (P<0.001) depressed at H+2 (18±10%) and D+2 (13±10%). During contraction, FL shortened and PA increased progressively with the increase in target torque and reached, respectively, -51.8±3.8% and +82.7±14.0% of initial values at MVC. FL increased and PA decreased significantly during MVC after the session and remained enhanced until D+4. Distal TE during MVC decreased immediately after the session (-20.6±23.1%; P<0.01) and recovered its initial value at H+2. After the training session, passive torque recorded during stretching increased for ankle angle of 25° (+35.3±38.7%; P<0.01) and 30° (+27.2±34.9%; P<0.01). Passive torque values returned to baseline at H+2, but re-increased at D+4. No significant changes were recorded after the session for FL, PA and TE. Discussion: The new finding is that the drop in MVC torque after eccentric contractions is associated with an increase in FL and a decrease in PA and TE, whereas the enhancement in passive torque during stretching is not associated with changes in muscle architecture and tendon elongation. In conclusion, a session of eccentric contractions did influence the components associated with muscle contraction but did not affect the passive components of the muscletendon unit.